2009
DOI: 10.4161/derm.1.4.9501
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles and their interactions with the dermal barrier

Abstract: The dermal application of drugs is promising due to the ease of application. In this context nano-scale carrier systems were already evaluated in several studies with respect to the skin interaction and the impact on drug penetration. At the same time the upcoming production of engineered nano-scale materials requires a thorough safety evaluation. Drug delivery as well as risk assessment depends crucially on the ability of such carriers to overcome the skin barrier and reach deeper tissue layers. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
213
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(224 citation statements)
references
References 73 publications
4
213
0
7
Order By: Relevance
“…As nanoparticles have molar masses in the order of 10 6 Da and greater, no significant transport over an intact dermal barrier is to be expected for human beings (Schneider et al, 2009). In that sense, nanoparticles lower than 300 nm show penetration most likely along two possible routes: the intercellular route, following lipid channels between corneocytes to deeper skin layers and the appendage route though hair follicles and sweat glands (Schneider et al, 2009;Rancan et al, 2012). Therefore, HALys nanoparticles present a suitable mean size for topical application and penetration may occur though lipid channels between corneocytes, hair follicles or sweat glands.…”
Section: Preparation Of Ha-lys Nanoparticlesmentioning
confidence: 99%
“…As nanoparticles have molar masses in the order of 10 6 Da and greater, no significant transport over an intact dermal barrier is to be expected for human beings (Schneider et al, 2009). In that sense, nanoparticles lower than 300 nm show penetration most likely along two possible routes: the intercellular route, following lipid channels between corneocytes to deeper skin layers and the appendage route though hair follicles and sweat glands (Schneider et al, 2009;Rancan et al, 2012). Therefore, HALys nanoparticles present a suitable mean size for topical application and penetration may occur though lipid channels between corneocytes, hair follicles or sweat glands.…”
Section: Preparation Of Ha-lys Nanoparticlesmentioning
confidence: 99%
“…99 However, it has been reported that some nanoparticles may cause adverse side effects. [100][101][102] Further study to ensure their safety for medical application is necessary. Although using a transgenic approach for tendon repair is an attractive possibility, one serious concern is how to turn off the function of a transgene after tendon repair.…”
Section: Tendon Injury and Repairmentioning
confidence: 99%
“…Although, a transfollicular penetration of particles could be observed when the skin barrier was strongly disrupted [9], several other studies demonstrated that particles of this dimension do not pass the intact barrier of the hair follicles [5,15,16], Therefore, loading of the particles with a drug represents an efficient opportunity to transport the drug into the hair follicles provided that, after reaching the specific depth within the hair follicles, the drug is released from the particles to penetrate independently through the intact barrier of the hair follicles, as shown previously [17].…”
Section: Introductionmentioning
confidence: 99%